No todo el tiempo se toca la caja. The temporality of materials in construction in Nazareno (Salta, Argentina) - Veliz, Natalia (2024)
The article develops the temporality of construction practices within the framework of an understanding of time that involves different dimensions, which allows us to understand how this is constitutive of architecture. It focuses on northern Argentina, on a set of Coya communities, which have agro-pastoral practices, which implies a particular production of the territory. The ethnographic methodology allows an approach to the processes from the perspective of the builders themselves. This look at the construction forms in the Andes makes it possible to understand that the making of materiality is not linear, but has to do with cyclical logic and a network of relationships, knowledge and transfers over time.